Evaluation of Moore and grab sampling method for Salmonella Typhi detection in environmental samples in Ghana - Michael Owusu; Eric Darko; Debora Akortia; Gifty Nkrumah; Sampson Twumasi-Ankrah; Michael Owusu-Ansah; Christopher B. Uzzell; Jonathan Rigby; Catherine M. Troman; Nicolette A. Zhou; John Scott Meschke; Alexander G. Shaw; et al. (PLoS ONE, 2025)
Background Typhoid fever causes substantial mortality and morbidity in low and middle-income countries (LMICs) as a result of inadequate water, hygiene, and sanitation facilities. The gold standard for typhoid diagnosis is blood culture, however this method is expensive and mostly unavailable in LMICs. Environmental surveillance (ES) could offer a low cost alternative to identify circulation of Salmonella enterica serovar Typhi (S.Typhi) and help inform public health interventions including vaccination. Methods We implemented standardized protocols for ES at 40 validated sites in peri-urban communities in Ghana from July 2022 to August 2023. Grab samples (GS) and Moore swabs (MS) were collected monthly for the initial 6 months and subsequently monthly MS were maintained for the rest of the study period. Wastewater samples were tested for S . Typhi target genes ( ttr, staG, tviB ) and a biomarker of human faecal contamination (Bacteroides HF183) using multiplex quantitative PCR (qPCR). Clinical surveillance for typhoid fever was performed by blood culture of febrile cases presenting to the local hospital who lived in the study area. Results For the first 6 months of wastewater ES, we observed a higher prevalence of S . Typhi in MS compared to GS [100/240 (42%; 95% Confidence Interval [CI]: 34-50% vs. 24/240 (10%; 95% CI: 6-16%)]; p-value < 0.001]. Overall, the detection of S. Typhi throughout the study period based on MS was 42.1% (202/480; 95% CI: 35-50%). The prevalence of S. Typhi in blood culture surveillance was 0.21% [12/5,576; 95% CI: 0.12-0.38%]. Precipitation (1.1 (95% CI: 1.02-1.10) and number of wet days (2.0 (95%CI: 1.40-2.88) were positively associated with an increased odds of S. Typhi detection in MS and GS. Conclusion Generally the proportion of S.Typhi detections in wastewater samples was less than blood culture-based detections. Limited detection of confirmed typhoid fever cases at the local hospital may reflect healthcare seeking behaviours, access as well as early treatment with over-the-counter antibiotics. Further work is required to confirm these qPCR detections with amplicon sequencing methods. Strategies also needs to be developed for integration of ES into public health decision making for the prevention of typhoid fever.